Waste Service Retribution Management in Selayar Islands Regency through Website-Based Solutions - Wisda; Nuraida Latif; Apriana, Rezki; Neneng Awaliah; Kumar Vivek; Kamaruddin (Ceddi Journal of Information System and Technology (JST), 2024)
The waste retribution management system at the Environmental Service office in Selayar Islands Regency is currently suboptimal. Customers are required to register for waste collection in person at the office, and the payment process must be done through a collection officer who visits the customer's location. Additionally, there is no formal channel for customers to provide feedback on the waste services they receive. To address these issues, an application is proposed to streamline waste service usage for the community and facilitate reporting for Environmental Service employees. The study aims to design and implement an Application for Data Collection and Reporting of Waste Service Retribution at the Environmental Service of Selayar Islands Regency. The research utilized field research, library research, interviews, and documentation to gather relevant data. The research methodology employed was Rapid Application Development (RAD), which involves stages such as requirements planning, user design, development, and implementation. The findings of the study suggest that the proposed application is highly feasible, based on the results of the respondents' assessments. This application is envisioned to significantly improve waste service management and customer experience in Selayar Islands Regency.